2021
DOI: 10.3389/fmars.2021.695753
|View full text |Cite
|
Sign up to set email alerts
|

Cellular, Hormonal, and Behavioral Responses of the Holothuroid Cucumaria frondosa to Environmental Stressors

Abstract: Holothuroids (sea cucumbers) are one of the most ubiquitous groups of benthic animals found across diverse marine ecosystems. As echinoderms, they also occupy an important place in the evolutionary hierarchy, sitting close to vertebrates in the deuterostome clade, making them valuable multidisciplinary model organisms. Apart from being ecologically and phylogenetically important, many species are commercially exploited for luxury seafood markets. With the global rise of aquaculture and fisheries, management an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
2
5
0
Order By: Relevance
“…the species studied in this research as C. frondosa was the biggest species compared to the other two. Other studies supported our results as the authors showed that higher coelomocyte counts and enhanced concentration of phagocytes were seen over time when C. frondosa was induced with stress [20,33]. In our result for differential cell count, we also saw that C. frondosa had a significantly high number of phagocytic cells, which could indicate a better immune response.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…the species studied in this research as C. frondosa was the biggest species compared to the other two. Other studies supported our results as the authors showed that higher coelomocyte counts and enhanced concentration of phagocytes were seen over time when C. frondosa was induced with stress [20,33]. In our result for differential cell count, we also saw that C. frondosa had a significantly high number of phagocytic cells, which could indicate a better immune response.…”
Section: Plos Onesupporting
confidence: 91%
“…Other studies supported our results as the authors showed that higher coelomocyte counts and enhanced concentration of phagocytes were seen over time when C . frondosa was induced with stress [ 20 , 33 ]. In our result for differential cell count, we also saw that C .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the number of hemocytes changes dramatically after live bacteria and viruses or microbial polysaccharides such as LPS, laminarin, and β1,3-glucan (i.e., M/PAMPs) are introduced into the body of invertebrates ( 12 14 , 22 ). This parameter has thus been used as a measure of stress and/or the physiological conditions of different species, including crustaceans ( 21 , 37 , 39 , 40 ). In the present study, injection of LPS into the body of P. scaber resulted in a rapid decrease in the numbers of free hemocytes (by 3 h), followed by recovery to the baseline control levels 6 h after challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In openwater, but with another species (H. poli), a recent study also observed significant growth, but low survival, of juveniles over 1 year (Cutajar et al 2022). Sea cucumbers are stresssensitive with physiological responses observed in response to environmental changes (Jobson et al, 2021;Hou et al, 2019;Kamyab et al, 2017). Performing a longer experiment allows the sea cucumbers to recover from environmental stress applied and acclimate to the new conditions.…”
Section: Survival Of H Tubulosa Below Fish Cagesmentioning
confidence: 99%